Risk Factor Analysis of Filariasis in Pidie Regency - Maifrizal Maifrizal; Teuku Reza Ferasyi; Fahmi Ichwansyah (JURNAL KESEHATAN LINGKUNGAN, 2023)
Introduction: Pidie Regency is a regency in Aceh Province with the second-highest number of filariasis patients in 2020. One of the risk factors for filariasis is the presence of stagnant water near houses which serves as the breeding ground and resting place for mosquitoes. Other risk factors for filariasis include the type of work, habit of leaving the house, and increased mosquito density. Methods: This quantitative study used a case-control study design. The participants of this study consisted of 126 individuals with 63 being filariasis patients (case subjects) and 63 being non-filariasis patients (control subjects). Results and Discussion: The results showed that education (OR = 3.86, p = 0.05), type of work (OR = 1.30, p > 0.05), presence of stagnant water (OR = 1.05, p > 0.05), and habit of leaving the house (OR = 1.4, p > 0.05) had significant relationships with the incidence of filariasis or elephantiasis in Pidie Regency in 2022. Conclusion: The results showed that education was the most significant risk factor for filariasis (OR = 60.87). This suggested that individuals with a lower level of education had a higher chance of contracting the disease. Another factor that influenced the incidence of filariasis was the presence of animals around the house (OR = 18.97). This suggested that individuals who had pets were 60.87 times more likely to get filariasis (p = 0.017).